Patient-reported short-term results of laparoscopic groin hernia repair: A multicenter prospective observational study from Japan - Saseem Poudel; Yoshihiro Ikeda; Tatsuya Tazaki; Seiya Susumu; Toshikatsu Nitta; Shinichi Yoshioka; Masaki Wakasugi; Masaru Matsumura; Tadashi Ohnishi; Kaisuke Yamamoto; Satoshi Hirano (International Journal of Abdominal Wall and Hernia Surgery)
INTRODUCTION: Hernia outcome reports in Asia remain sparse compared to Western counterparts. This multicenter prospective observational study aimed to assess the short-term outcomes of laparoscopic groin hernia repair in Japan. METHODS: This study included adult patients undergoing laparoscopic groin hernia repair surgery for primary unilateral hernias at participating institutes from March 2021 to November 2022. Patients with previous surgery in the lower abdomen or with scrotal hernia were excluded. At the ward or during follow-up clinic visits, the patients were given a printed copy of the questionnaire that we developed to assess pain intensity, daily life interference, and surgical outcomes. This was administered before surgery, at 1 week, 1 month, and 3 months postoperatively, which they then completed and submitted. The primary outcome was complication rate at the end of the 3-month postoperative period. RESULTS: A total of 1,467 cases from 21 institutes were registered. The response rate at the end of 3 months after the surgery was 87.1%. Nearly 70% of the surgeries were performed by surgeons with an experience of over 500 cases. The average operation time was 74.6 ± 27.6 min with a negligible rate of intraoperative complications. No complications above Clavien–Dindo Grade II were reported. Short-term outcomes indicated low rates of chronic pain (0.16%) and seroma (1.7%) and high patient satisfaction (98.27%). CONCLUSION: Our study provides valuable insights into the short-term outcomes of laparoscopic groin hernia repair from multiple institutes in Japan, demonstrating favorable results with low complication rates and high patient satisfaction. TRIAL REGISTRATION: The study was registered in UMIN-CTR (https://www.umin.ac.jp/ctr/index-j.htm registration number: UMIN000043184).